Multidimensional Short Tools to assess frailty: a narrative review - Formosa, V.; Lorusso, G.; Lentini, G.; Terracciano, E.; Gentili, S.; Liotta, G. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The population of the European Union is progressively ageing, therefore frailty is becoming a crucial public health issue. In recent years there is a growing interest in a multidimensional concept of frailty, that is not only physical but also psychological and social, in line with a person-centered care. Study design. To measure frailty represents a fundamental step to evaluate the needs for care at both population and individual levels. Of course, to assess frailty in a large population is essential to find short and quick tools able to give reliable results in terms of risk of occurrence of negative events, to stratify older adults according to their frailty level. In this way the most appropriate strategies can be chosen and applied, to delay the functional decline associated to frailty and its consequences, such as hospitalization, institutionalization, low quality of life, and death.Methods. In this review we searched on PubMed for articles about scales assessing frailty with peculiar characteristics: published for the first time in 2010, available in English, with a short length and duration of administration, composed by multidimensional domains.Results. Seven scales were found and analyzed: The Zulfiqar Frailty Scale (ZFS), The Pictorial Fit-Frail Scale (PFFS), The Tilburg Frailty Indicator (TFI), The SUNFRAIL Tool, The (fr)AGILE, The Risk Instrument for Screening in the Community (RISC) and The Short Functional Geriatric Evaluation (SFGE). We compared their main features as the number of questions, the time for administration, the domains used and the psychometric properties as validity and reliability, with the aim of providing a set of useful information to health professionals in their everyday work.Conclusions. The use of these tools provides important information to help plan community health and social care and meet individuals’ needs for care, but this approach is not common for community care in the EU yet.